Learning Management of Islamic Religious Education for Children with Intellectual Disabilities: Multicase Study - Maulida Ulfa; Salminawati; Zaini Dahlan (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to examine the learning of Islamic Education for children with intellectual disabilities in Sekolah Luar Biasa (SLB) Negeri Binjai and Sekolah Luar Biasa Negeri 1 Binjai, including planning, implementation, learning evaluation, as well as barriers and solutions in learning. The research method uses a qualitative approach with a multi-site study to explore the learning process at SLB Negeri Binjai and SLB Negeri 1 Binjai The research findings indicate that Islamic Education learning in both SLBs includes the introduction of basic Islamic concepts, teaching methods tailored to the needs of students, and parental involvement in the learning process. However, there are still obstacles such as limited resources and a lack of training for Islamic Education teachers. In conclusion, this research provides a significant contribution to efforts to improve the quality of Islamic education for children with special needs SLB Negeri Binjai and SLB Negeri 1 Binjai.